Private Tutoring Expenditures in Turkey - Aysit Tansel; Fatma Bircan (Institute for the Study of Labor (IZA), 2004)
This is the first study on private tutoring in Turkey. Private tutoring especially for the purpose of preparing for the competitive university entrance examination is an important, widespread phenomenon in Turkey. Private tutoring centers are commonly referred to as "dersane" in Turkish. This study first gives an overview of private tutoring centers. Next, it examines the determinants of private tutoring expenditures in Turkey using the results of the 1994 Household Expenditure Survey. The determinants examined within a Tobit model framework include total household expenditure, education levels of parents and other household characteristics. Such analysis of the household behavior of attempting to provide better education to their children will highlight the determinants of the demand for education and the intergenerational transfers in Turkey.
Keywords: I21; R20; I22; I20; 330; private tutoring; education; demand for education; Privatschule; Bildungsverhalten; Bildungsfinanzierung; Generationenbeziehungen; Schätzung; Türkei